Spatio-Temporal Clustering for Optimizing Time-Sensitive Product Deliverie - Chamansingh, Nicholas; Hosein, Patrick; Dyer, Elena (International Journal of Operational Research/Nepal, 2019)
We consider the problem of optimizing the near-periodic delivery of a product to customers with the additional constraint that there is an estimated deadline for delivery of the product. Delivery after the deadline is unacceptable while early delivery increases the frequency of deliveries which is also not desirable. While satisfying these customer constraints we wish to minimize the resources required by the delivery company to provide this service. In particular, we wish to minimize the total travel distance for delivery of products to customers since this reflects the associated costs of the service.